The Wayward Bus Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Johnny Chicoy (Rick Jason) holds the arm of Alice Chicoy (Joan Collins) as she gets on the bus. RESTRICTED USE